Growth, Biomass Production and Dry Matter Distribution Pattern of Eucalyptus Hybrid Grown in an Energy Plantation - Pal, Mohinder; Raturi, D. P. (Indian Forester, 1991)
The preeent Investigation waa undertaken to study the growth, biomass production, dry matter distributIon pattern and inter-relationship between the various yield contributes of biomass of Eucalyptus hybrid grown in an energy plantation, under rain-fed conditions In semi-acid zone. The age of plantation was three years. The growth of individual trees in the plantatIon was very heterogeneous. The tree height varied from 550 cm to 990 cm and girth at breast height varied from 5 cm to 35 cm. Although the larger trees, or category A trees, were much fewer in number than the medium size and smaller trees of category B and category C, their contribution to biomass yield was maximum. Further, the biomass of category A trees was superior even qualitatively since it contained higher percentage of bole-wood and utilizable biomass and less at non-utilizable biomass. The total blomsss yield was 44.78 oven-dry tonne per hectare. Bole and brenches constitute the major yield contributes of biomass.